Instagram Story Sebagai Media Self Disclosure - Yahya, Firmansyah; Kurniawan, Achmad Wildan; Sukmawati, Irma (Jurnal Komunikasi Universitas Garut: Hasil Pemikiran dan Penelitian, 2024)
Abstract This research is motivated by the large number of Instagram users who do not hesitate to express themselves by publishing personal things on Instagram stories, such as sharing their life problems, sharing their daily activities regularly such as taking photos of lunch menus, the clothes they wear, sharing locations, and so on. The aim of this research is to explain the motives, experiences and meaning of self-disclosure on social media Instagram stories in generation Z aged 18 to 24. This research uses a qualitative approach with descriptive methods and uses phenomenological theory. The data collection techniques used were observation, interviews, literature study and documentation. Determining the research subjects used a purposive sampling technique with 7 informants who were generation Z aged 18 to 24 years and 3 sources from different professional fields. The research results show that the motive for generation Z aged 18-24 years in carrying out self-disclosure on Instagram story social media is because they need recognition, because they do not have a place to tell stories and as a memory archive. Generation Z's motive for self-disclosure on Instagram stories is to express themselves, clear themselves, and share stories or information. The positive experiences they experience are feeling calm, relieved and happy, improving communication relationships, being better understood by others and becoming self-branding. Meanwhile, the negative experiences they experienced were causing envy, causing misunderstandings, causing feelings of anxiety and getting hate comments. The meaning of self-disclosure on Instagram stories for generation Z aged 18-24 has its own meaning depending on the experiences they have experienced, namely as a medium for expressing themselves, a form of self-love, a medium for disclosing self-information, improving communication relationships, increasing self-confidence and as a form of everyone's rights. insiders utilize their social media. Keywords: Self-disclosure; instagram stories, generation Z. Abstrak Penelitian ini dilatarbelakangi oleh banyaknya pengguna instagram yang tanpa ragu melakukan pengungkapan diri dengan mempublikasikan hal pribadi pada instagram story, seperti membagikan permasalahan hidupnya, membagikan aktivitas sehari-harinya secara rutin seperti memfoto menu makan siang, pakaian yang dipakai, berbagi lokasi, dan lainnya. Tujuan penelitian ini adalah untuk menjelaskan motif, pengalaman dan makna pengungkapan diri di media sosial instagram story pada generasi Z usia 18 hingga 24. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif dan menggunakan teori fenomenologi. Teknik pengumpulan data yang digunakan yaitu observasi, wawancara, studi pustaka, dan dokumentasi. Penentuan subjek penelitian menggunakan teknik purposive sampling dengan 7 informan yang merupakan generasi Z usia 18 hingga 24 tahun serta 3 narasumber dari bidang profesi yang berbeda. Hasil penelitian menunjukkan bahwa motif karena generasi Z usia 18-24 tahun dalam melakukan self disclosure di media sosial instagram story adalah karena membutuhkan pengakuan, karena tidak memiliki tempat untuk bercerita dan sebagai arsip memori. Motif untuk generasi Z dalam melakukan self disclosure di instagram story adalah untuk mengekspresikan diri, menjernihkan diri, dan berbagi cerita atau informasi. Pengalaman positif yang mereka alami adalah mendapatkan perasaan tenang, lega dan bahagia, meningkatkan hubungan komunikasi, menjadi lebih dipahami oleh orang lain dan menjadi self branding. Sedangkan untuk pengalaman negatif yang mereka alami adalah menimbulkan sifat iri, menimbulkan kesalahpahaman, menimbulkan perasaan cemas dan mendapatkan hate comment. Makna self disclosure di instagram story bagi generasi Z usia 18-24 memiliki pemaknaannya masing-masing tergantung pengalaman yang mereka alami yakni sebagai media mengekspresikan diri, bentuk self love, media mengungkapkan informasi diri, meningkatkan hubungan komunikasi, meningkatkan percaya diri dan sebagai bentuk hak setiap orang dalam memanfaatkan media sosialnya. Kata-kata kunci: Pengungkapan diri; instagram story, generasi Z.